Genetic Suspects : Global Governance of Forensic DNA Profiling and Databasing - Hindmarsh, Richard; Prainsack, Barbara (Cambridge : Cambridge University Press, 2010)
As DNA forensic profiling and databasing become established as key technologies in the toolbox of the forensic sciences, their expanding use raises important issues that promise to touch everyone's lives. In an authoritative global investigation of a diverse range of countries, including those at the forefront of these technologies' development and use, this book identifies and provides critical reflection upon the many issues of privacy; distributive justice; DNA information system ownership; biosurveillance; function creep; the reliability of collection, storage and analysis of DNA profiles; the possibility of transferring medical DNA information to forensics databases; and democratic involvement and transparency in governance, an emergent key theme. This book is timely and significant in providing the essential background and discussion of the ethical, legal and societal dimensions for academics, practitioners, public interest and criminal justice organisations, and students of the life sciences, law, politics, and sociology.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: DNA fingerprinting; DNA Fingerprinting